Global climate imprint on seismic noise - Stutzmann, E.; Schimmel, Martin; Patau, G.; Maggi, A. (Geochemistry, Geophysics, Geosystems, 2009)
In the absence of earthquakes, oceanic microseisms are the strongest signals recorded by seismic stations. Using the GEOSCOPE global seismic network, we show that the secondary microseism spectra have global characteristics that depend on the station latitude and on the season. In both hemispheres, noise amplitude is larger during local winter, and close to the equator, noise amplitude is stable over the year. There is an excellent correlation between microseism amplitude variations over the year and changes in the highest wave areas. Considering the polarization of the secondary microseisms, we show that stations in the Northern Hemisphere and close to the equator record significant changes of the secondary microseism source azimuth over the year. During Northern Hemisphere summer, part or all of the sources are systematically located farther toward the south than during winter. Stations in French Guyana (MPG) and in Algeria (TAM) record microseisms generated several thousand kilometers away in the South Pacific Ocean and in the Indian Ocean, respectively. Thus, secondary microseism sources generated by ocean waves which originate in the Southern Hemisphere can be recorded by Northern Hemisphere stations when local sources are weak. We also show, considering a station close to Antarctica, that primary and secondary microseism noise amplitudes are strongly affected by changes of the sea ice floe and that sources of these microseisms are in different areas. Microseism recording can therefore be used to monitor climate changes. This is IPGP contribution 2556. M.S. acknowledges IPGP and the consolider-ingenio 2010 program CSD 2006-00041. The authors thank GEOSCOPE for making data available. Computations were done using the EGEE data grid facilities, and the authors thank David Weissenbach for his help. Peer reviewed